Relationship between the methylenetetrahydrofolate reductase (MTHFR) rs1801133 SNP and serum homocysteine levels of Zhuang hypertensive patients in the central region of Guangxi - Xi-Jiang Hu; Mei-Ru Su; Bao-Wei Cao; Fa-Bang Ou; Rui-Xing Yin; An-De Luo (BMC, 2023)
Abstract Background The relationship between the methylenetetrahydrofolate reductase (MTHFR) single nucleotide polymorphism (SNP) and serum homocysteine (Hcy) levels or H-type hypertension in different populations is inconsistent. This study aimed to explore the association between the MTHFR rs1801133 SNP and serum Hcy levels of Zhuang hypertensive patients in the central region of Guangxi. Methods A total of 606 Zhuang inpatients with essential hypertension were recruited in our hospital from August 2016 to December 2018. The patients were divided into H-type hypertension (Hcy > 10 µmol/L, n = 528) and non-H-type hypertension (Hcy ≤ 10 µmol/L, n = 78) groups. At the same time, an age- and sex-matched group of 379 subjects with normal physical examination in our hospital were selected as the control group. Blood biochemical measurements and genotyping of the MTHFR rs1801133 SNP were performed. Results The prevalence of H-type hypertension was 87.13%. The levels of serum Hcy in patients with hypertension were higher than those in control group (14.20 ± 5.78 μmol/L vs. 11.97 ± 5.39 μmol/L, P < 0.001), especially in patients with H-type hypertension (15.08 ± 5.65 μmol/L, P < 0.001). The frequencies of TT genotype (22.73%) and T allele (46.21%) in patients with H-type hypertension were significantly higher than those in control group (11.35% and 30.47%, respectively) and non-H-type hypertension group (10.26% and 28.85%, respectively; P < 0.001 for all). Multivariate linear regression analysis showed that serum Hcy levels were significantly correlated with creatinine, low-density lipoprotein cholesterol, endogenous creatinine clearance rate, and the MTHFR rs1801133 genotypes in control group, while serum Hcy levels were significantly correlated with creatinine, triglyceride, low-density lipoprotein cholesterol, endogenous creatinine clearance rate, glycosylated hemoglobin, and the MTHFR rs1801133 genotypes in H-type hypertension group (P < 0.05-0.001). Serum Hcy levels in the T allele carriers were higher than those in the T allele noncarriers in both H-type hypertension and control groups. Conclusions There was closely related between the MTHFR rs1801133 SNP and serum Hcy levels in Zhuang patients with H-type hypertension in the central region of Guangxi. The MTHFR SNP may be an important reason for the increase of serum Hcy levels in Zhuang patients with H-type hypertension in this region.